Performance Analysis Stability Of Speed Control Of BLDC Motor Using PID-BAT Algorithm In Electric Vehicle - Izza Anshory (JEEE-U (Journal of Electrical and Electronic Engineering-UMSIDA), 2017)
The research on the development of electric vehicles includes such as power electronics, energy storage capability that the higher the battery, reducing fuel emissions, and the motor efficiency. The electric motor efficiency requires the automatic control on the main parameters such as speed, position, and acceleration. The performance setting of speed Brushless DC (BLDC) Motor can be improved by using the controller Proportional Integral Derivative (PID), a combination of PID using nature inspired optimization algorithms such as Bat Algorithm (BA). BA is one of the optimization algorithm that mimics the behavior of bats on the move using a vibration or sound pulses emitted a very loud (echolocation) and listen to the echoes that bounce back from the object to determine the circumstances surrounding vicinity In this paper, simulate of Bat Algorithm to find the best value PID controller parameter to speed control BLDC motor and analyze performance such as the value of overshoot, steady state. The result simulation shows that values for the PID parameters without using algorithm bat is Kp = 208.1177, Ki = 1767, and Kd = -8.6025. While using the algorithm bat got value Kp = 5.4303e+04, Ki = -1.3059e+06, and Kd = 3.0193e+04. The performance of the motor obtained through value rise time of 0. 282, settling time of 1.5, overshoot value of 20.5% and the peak value of 1.21.